The effects of noise on biochemical parameters using rat's hearts - Rahma, Muayad Salm; Win, Ni N.; Rafidah, H. M.; Ailin, Razali (EuroJournals, 2011)
The present study was undertaken to evaluate the effect of acute and chronic high intensity noise on plasma blood glucose concentration and lipid profile of rats. The rats were divided into four groups and they include exposure to noise of intensity 80-100 dBA on duration of 12 hours exposure (acute effect), 8 hours daily for 20 days (chronic effect), 20 days into 3 days exposure and 2 days without 8 hours per day (intermittent effect) and the control group. Noise of 80-100 dBA was found to cause significant increase in plasma glucose for the acute and chronic continuous groups as compared to no noise exposure. The cholesterol, triglycerides (TG) and high density lipoprotein (HDL) had no significant difference compared to control. HDL level revealed significant elevation in case of chronic continuous and intermittent noise exposure (p < 0.05) when compared to control group. In conclusion the present study determined that high intensity noise may have an adverse effect on biochemical values and thus noise exposure should be well monitored.